2024
DOI: 10.1089/neu.2023.0309
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Effects of Repeated Blast Exposure in Special Operations Personnel

James R. Stone,
Brian B. Avants,
Nicholas J. Tustison
et al.

Abstract: Exposure to blast overpressure has been a pervasive feature of combat-related injuries. Studies exploring the neurological correlates of repeated low-level blast exposure in career “breachers” demonstrated higher levels of tumor necrosis factor alpha (TNFα) and interleukin (IL)-6 and decreases in IL-10 within brain-derived extracellular vesicles (BDEVs). The current pilot study was initiated in partnership with the U.S. Special Operations Command (USSOCOM) to explore whether neuroinflammation is seen within sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Thus, our TSPO PET findings within the rACC do not distinguish specific changes in neuroimmune function from broader alterations in cellular metabolism. A key future direction will be to elucidate the pathophysiological mechanisms and temporal dynamics underlying the relationship between neuroimmune function, cellular metabolism, and astroglial scarring at the gray-white matter junction, particularly given emerging evidence of neuroinflammation in SOF personnel ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our TSPO PET findings within the rACC do not distinguish specific changes in neuroimmune function from broader alterations in cellular metabolism. A key future direction will be to elucidate the pathophysiological mechanisms and temporal dynamics underlying the relationship between neuroimmune function, cellular metabolism, and astroglial scarring at the gray-white matter junction, particularly given emerging evidence of neuroinflammation in SOF personnel ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…13 Interestingly, in a different cohort of active-duty SOF, higher blast exposure was associated with increased TSPO signal in the salience network. 15 The discrepancy in findings across these two studies 13,15 may have been due to the use of a different tracer (i.e., [18F]DPA-714), a different statistical analytic approach (i.e., applying dimensionality reduction before testing the association between biomarkers and blast exposure), or a different study design (i.e., comparing blast-exposed special operators to non-exposed matched controls). Overall, the present work illustrates the potential neurobehavioral consequences of network-level disruptions in a population heavily exposed to blast and blunt head trauma.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Trotter et al [ 71 ], Veterans with a history of blast exposure not only showed a similar graded association via DTI but also demonstrated a more rapid decline in white matter integrity with age compared to unexposed individuals, indicating that cumulative blast exposure may contribute to an accelerated aging process. A recent study by Stone et al [ 34 ] supports these findings, revealing that special operators with repeated LLB exposure show elevated PET-neuroinflammation, a characteristic of neurovascular dysfunction and contributor to the progression of neurodegenerative diseases such as Alzheimer’s disease (AD), Parkinson’s disease (PD), and amyotrophic lateral sclerosis (ALS) [ 72 ].…”
Section: The Use Of Neuroimaging In Blast-related Neurotrauma Researchmentioning
confidence: 95%
“…The cell-to-cell communication is vital for maintaining BBB integrity and regulating CBF [ 32 , 33 ]. While it is difficult to isolate the pathological effects of LLB in humans, studies focused on cumulative wall breaching and mbTBI have analyzed neuroimaging and serum biomarkers to better understand the mechanisms of blast-induced brain injury [ 13 , 29 , 34 ]. Simultaneously, numerous preclinical studies have been performed to study primary blast overpressure as the main experimental variable.…”
Section: Neurovascular Dysfunction Following Low-level Blast Exposurementioning
confidence: 99%